Immunohistochemistry in the diagnosis of yellow fever - MUÑOZ, ELENA (2004)
Objective: To determine the presence of yellow fever virus antigen in liver samples. Material and Methods: Immunohistochemistry assay was used in liver samples obtained from 34 patients from 1999 through 2002; they lived in different regions of the country and presented clinical diagnosis of yellow fever. Monoclonal and polyclonal antibodies against yellow fever virus and biotin-streptavidin complex were applied to liver sections (paraffinized-liver). A liver sample from a patient with serological and histophatological diagnosis of yellow fever was used as positive control and a negative control was a liver sample obtained at necropsy from a patient without liver disease. Results: Brown staining of the liver cell cytoplasm was considered positive. The presence of yellow fever virus antigen was confirmed in the 34 liver samples studied from 1999 to 2001. Patients came San Martín, Junín, Cuzco, Loreto, Pasco and Ucayali departments. Conclusion: Immunohistochemistry assay is a useful diagnostic tool for epidemiologic studies due to its high sensitivity and specificity (90%), when a retrospective diagnosis may be performed.